Can chlorophyll fluorescence be used to determine the optimal time to harvest rice seeds for long-term genebank storage?. Issue 3 (September 2015) - Hay, Fiona R.; Timple, Stephen; van Duijn, Bert
Abstract Chlorophyll fluorescence (CF) analysis was explored as a potential tool to identify the optimal time to harvest rice seed germplasm for maximum storage longevity. Seeds of 20 diverse genebank accessions were harvested at 24, 31, 38 and 45 d after peak flowering (DAF) and half of each seed lot was sorted by hand, following normal practice at the T.T. Chang Genetic Resources Center. CF analysis was carried out on both non-sorted and sorted seeds, while storage experiments were carried out on sorted seeds. Seed longevity (the time for viability to fall to 50%, p50) was significantly correlated with the skewness, kurtosis, mode and mean of the CF histograms when the data for every accession at all the harvest times were included in the correlation analysis. However, these correlation coefficients were ≤ 0.481. The correlation coefficient between p50 and DAF was similarly low (0.461). For individual accessions, there was wide variation in the correlation coefficients. While for some accessions, there appeared to be a strong relationship between p50 and mean CF that could be used to guide when to harvest seeds in the field, for other accessions, a unique mean CF to inform when to harvest seeds or for use in seed sorting could not be identified; this was also true for DAF over the harvesting schedule used in this study. Given the number and diversity of accessions managed by a genebank, it seems unlikely that CF analysis would be an appropriate tool to help manage the regeneration or processing of seeds intended for storage in the genebank.